Neurophysiological and Behavioral Responses to Music Therapy in Vegetative and Minimally Conscious States - O'Kelly, Julian; James, L.; Palaniappan, R.; Fachner, J.; Taborin, J.; Magee, W.L. (Frontiers in Human Neuroscience, 2013)
Assessment of awareness for those with disorders of consciousness (DOC) is a challenging undertaking, due to the complex presentation of the population, where misdiagnosis rates remain high. Music therapy may be effective in the assessment and rehabilitation with this population due to effects of musical stimuli on arousal, attention and emotion, irrespective of verbal or motor deficits, however, an evidence base is lacking. To address this, a neurophysiological and behavioural study was undertaken comparing EEG, heart rate variability, respiration and behavioural responses of 20 healthy subjects with 21 individuals in vegetative or minimally conscious states (VS or MCS). Subjects were presented with live preferred music and improvised music entrained to respiration (i.e., music therapy procedures), recordings of disliked music, white noise and silence. ANOVA tests indicated a range of significant responses (p ≤ 0.05) across healthy subjects corresponding to arousal and attention in response to preferred music including concurrent increases in respiration rate with globally enhanced EEG power spectra responses across frequency bandwidths. Whilst physiological responses were heterogeneous across patients, significant post hoc EEG amplitude increases for stimuli associated with preferred music were found for frontal midline theta in 6 VS and 4 MCS subjects, and frontal alpha in 3 VS and 4 MCS subjects (p = 0.05 - 0.0001). Furthermore, behavioural data showed a significantly increased blink rate for preferred music (p = 0.029) across the VS cohort. Two VS cases are presented with concurrent changes (p ≤ 0.05) across measures indicative of discriminatory responses to both music therapy procedures. A MCS case study highlights how more sensitive selective attention may distinguish MCS from VS. Further investigation is warranted to explore the use of music therapy for prognostic indicators, and its potential to support neuroplasticity in rehabilitation programmes.